An integrated approach to modelling end-use energy and water consumption of Australian households. (October 2016) - Ren, Zhengen; Chan, Wan Yee; Wang, Xiaoming; Anticev, Julia; Cook, Stephen; Chen, Dong
Abstract: To predict both end-use energy and water consumption of households, an integrated approach was developed by adding water module into the AusZEH design tool, which was a physically-based model to simulate energy consumption of residential buildings considering building envelop, appliance characteristics, local climate and occupant behaviour. Water and its associated energy consumption includes indoor and outdoor water systems considering actual operation of the water systems. Monte Carlo approach was applied to simulate both energy and water use patterns of appliances considering uncertainties. The comparisons between simulation and actual data show the model can track both energy and water consumption and usage patterns.